(untitled) (Journal of Dhaka Medical College, 2020)
Background: Inappropriate use of antimicrobials results in development of resistance to antibiotics. Aims and objectives: The present study was aimed at evaluating the current trends in prescribing antimicrobials in patient sufferings from ENT infection. Methods: A descriptive cross sectional study was carried out at ENT out-patient department of Khulna Medical College Hospital for three months in which data were collected from 500 prescriptions in customized proforma and analyzed using the World Health Organization (WHO) prescribing indicators. Results: Majority of the patients were females (55%) which was commonly seen between the age group of 15-24 years (39.2%).The most common diseases reported was Recurrent tonsillitis (16.4%) followed by Pharyngitis (15%), CSOM (13.2%). Commonly prescribed oral antimicrobials were â-lactams(39.72%) followed by fluroquinolones 16.16% and macrolides(4.98%). Among the â-lactams, Cefuroxime+clavulenic acid(20.39%) was more used followed by amoxicillin+clavulanic acid(15.55%), and among fluroquinolones was ciprofloxacin 9.81%and among macrolides was azithromycin(4.98%). 57.70% patients received single antimicrobials whereas 42.3% received multiple antimicrobials. Average number of antimicrobials prescribed per patient being 1.32. Concomitant therapy included antihistamines(22.93%), Nasal decongestant(21.56%). Average number of drugs per prescription was 3.07. All drugs were prescribed in brand names. Oral and topical preparations were frequently prescribed rather injection prescribed was nil. Percentage of encounters with an antibiotic prescribed was100%. and only 28..72% drugs were prescribed from Essential Drug List of Bangladesh 2008. Conclusion: Prescribing multiple antimicrobials in this study without definite culture and sensitivity reports make the study less rational in accordance with the standard guidelines. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 155-160